Cytosolic and microsomal glutathione S-transferase isoenzymes in normal human liver and intestinal epithelium. Issue 6 (June 1989) - Hayes, P C; Harrison, D J; Bouchier, I A; McLellan, L I; Hayes, J D
Abstract : Glutathione S-transferases are a group of drug metabolising and detoxification enzymes. We have studied the distribution of four isoenzymes, acidic, basic, neutral, and microsomal GST in human liver, gall bladder, and small and large intestinal epithelium by immunohistochemistry. Antibodies were raised in rabbits to purified GST subunits and several formalin fixed paraffin sections of each human tissue studied using the peroxidase-antiperoxidase method. Staining density was graded from very strong (+++) to negative (-). All four enzymes were identified within the liver, the acidic GST being found almost exclusively within the biliary epithelium. The gall bladder epithelium stained strongly for acidic and basic GST. In the small intestinal epithelium the acidic and neutral GST were readily identified in villi and crypts, whilst basic GST was found only in the villi and microsomal only in the crypts. In the colonic mucosa only acidic GST could consistently be identified. This histological heterogeneity may have functional implications for these enzymes in human hepatobiliary and intestinal tissue.